Exploration of Polysaccharides and Oligosaccharides from Jali (Coix Lacryma-jobi) and Its Potential as Prebiotic - Arianty, Devi; Sutrisno, Aji; Krisna Wardani, Agustin (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
Jali (Coix lacryma-jobi) is a cereal plant widely used as a functional food because it contains carbohydrate compounds, such as polysaccharides and oligosaccharides with a positive impact on the digestive system. This study was divided into two stages, namely extraction Jali and prebiotic analysis. The extraction method used was hot water extraction and alkali extraction according to their solubility in solvents. The prebiotic activity of oligosaccharide and polysaccharide extracts from jali was evaluated using in-vitro analysis. Therefore, this study aimed to explore polysaccharides and oligosaccharides in jali and their potential to act as prebiotic. The results showed that the extraction process affected the types of oligosaccharides, namely Fructooligosaccharides (FOS), as well as polysaccharides, including α-glucan and arabinoxylan. In this study, FOS and α-glucan were obtained by heating at 80 °C for 60 minutes, while arabinoxylan was extracted by heating at 80 °C for 120 minutes. The results of crude extracts of FOS and arabinoxylan were tested for HPLC analysis, while α-glucan was explored using FTIR. The jali seeds exhibited a remarkable FOS content of 40.78%, while their arabinoxylan composition included 22.4% arabinose and 4.8% xylose. In addition, the FTIR analysis revealed the presence of (14) (16) -α-D-glucan bond in jali seeds. The results showed that the extraction from the polysaccharide group, namely α-Glucan and Arabinoxylan, as well as from the oligosaccharides (FOS) had potential as prebiotic for the growth of Bifidobacterium longum and Lactobacillus casei. However, the highest results were based on OD and SCFA from the FOS extract. The addition of FOS affected the growth of Bifidobacterium longum more significantly (OD 0,871) compared to Lactobacillus casei (OD 0,725). Bifidobacterium longum exhibited SCFA levels of 243,827 mmol/L, while Lactobacillus casei showed levels of 140,942 mmol/L.